2008
DOI: 10.1063/1.2839598
|View full text |Cite
|
Sign up to set email alerts
|

Leakage mechanisms in bismuth ferrite-lead titanate thin films on Pt∕Si substrates

Abstract: ( 1 − x ) Bi Fe O 3 – x Pb Ti O 3  (0.5<x<0.3) thin films have been reported to exhibit high remanent polarizations but device integration is hindered by the presence of leakage currents. An insight into the nature of leakage mechanisms in the films is presented. Films with x=0.4 and 0.5 exhibit lower leakage currents as compared to x=0.3 films. At applied fields above 190kVcm−1, in the region of the coercive field of these films, x=0.4 and 0.5 exhibit a Poole–Frenkel mechanism while films with x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 21 publications
5
37
0
Order By: Relevance
“…While practical applications prefer high quality BiFeO 3 thin films in heteroepitaxial form, a large amount of effort was devoted to thin films of BiFeO 3 [74][75][76][77][78][79][80] where the crystal structure is monoclinic rather than rhombohedral as seen in bulk ceramic samples, due to the strain of substrates. Nowadays, high quality BiFeO 3 epitaxial films with room-temperature polarization as high as 60~80 μC/cm 2 which approaches the theoretical value, are available [74,81].…”
Section: +mentioning
confidence: 99%
“…While practical applications prefer high quality BiFeO 3 thin films in heteroepitaxial form, a large amount of effort was devoted to thin films of BiFeO 3 [74][75][76][77][78][79][80] where the crystal structure is monoclinic rather than rhombohedral as seen in bulk ceramic samples, due to the strain of substrates. Nowadays, high quality BiFeO 3 epitaxial films with room-temperature polarization as high as 60~80 μC/cm 2 which approaches the theoretical value, are available [74,81].…”
Section: +mentioning
confidence: 99%
“…2 the PhAT model describes the lnJ against 1/T curves well. As noted above, the presence of a Poole-Frenkel conduction mechanism has been reported for (1−x)BiFeO 3 -xPbTiO 3 (0.5 < x < 0.3) thin films with x = 0.4 and x = 0.5 Khan et al [7]. The fit of that data to the PhAT model is displayed in Fig.…”
Section: Model and Comparison With Experimental Datamentioning
confidence: 82%
“…Despite the fact that electronic conduction properties of those structures have been studied in some works [3][4][5][6][7], the current nonlinear behavior and its temperature variation are not fully understood yet. For instance, Qi et al [3] asserted that the main conduction mechanism for pure and Ni 2+ doped BFO was a space charge limited current (SCLC), while Pabst et al [5] affirmed that the Poole-Frenkel (PF) emission was the predominant mechanism in the high quality epitaxial BFO film formed by pulsed laser deposition (PLD) symmetric SrRuO 3 /BFO/SrRuO 3 capacitors and no clear dominant current mechanism can be attributed for the asymmetric Pt/BFO/SrRuO 3 structures.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is reported that [9,13,14], in low voltage (or electric field) region, the leakage current behaviour introduced by thermal generated carriers would follow the Ohmic conduction mechanism. In detail, in low voltage region, the leakage current mainly comes from the thermal excitation of trapped electrons in films from one trap site to another.…”
Section: Experimental Methodsmentioning
confidence: 98%